2015
DOI: 10.1037/xan0000063
|View full text |Cite
|
Sign up to set email alerts
|

Factors modulating social influence on spatial choice in rats.

Abstract: Three experiments examined the conditions under which the spatial choices of rats searching for food are influenced by the choices made by other rats. Model rats learned a consistent set of baited locations in a 5 × 5 matrix of locations, some of which contained food. In Experiment 1, subject rats could determine the baited locations after choosing 1 location because all of the baited locations were on the same side of the matrix during each trial (the baited side varied over trials). Under these conditions, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…In fact, the choices made by the Subject Rats were strongly controlled by the choices of the Model Rats in this experiment. The results of the experiments reported by Bisbing et al (2015) considered as a whole strongly suggest that social information was used to locate food by the Subject Rats only when personal information (the outcome of the Subject Rats' own choices) did not specify the remaining baited locations. It suggests that social information controls behavior only when it is not redundant with personal information.…”
Section: Empirical Backgroundmentioning
confidence: 85%
See 4 more Smart Citations
“…In fact, the choices made by the Subject Rats were strongly controlled by the choices of the Model Rats in this experiment. The results of the experiments reported by Bisbing et al (2015) considered as a whole strongly suggest that social information was used to locate food by the Subject Rats only when personal information (the outcome of the Subject Rats' own choices) did not specify the remaining baited locations. It suggests that social information controls behavior only when it is not redundant with personal information.…”
Section: Empirical Backgroundmentioning
confidence: 85%
“…Under these conditions, rats tended to avoid visits to locations that had been previously visited (and thereby depleted of food) by the other rat, just as they do in the radial-arm maze. Bisbing et al (2015) reported four experiments using the Pit Maze. All of them involved a procedure in which only a subset of the 25 locations was baited on each trial.…”
Section: Empirical Backgroundmentioning
confidence: 98%
See 3 more Smart Citations